2021
DOI: 10.1111/jfpp.15218
|View full text |Cite
|
Sign up to set email alerts
|

Impact of the incorporation of date pit flour an underutilized biowaste in dough and its functional role as a fat replacer in biscuits

Abstract: Date pit (Phoenix dactylifera L.), an underutilized biowaste, is the major by-product of the date processing industry. Date pits (DPs) are the naturally rich sources of several bioactive compounds that play a vital role in the prevention of the diseases. In the present study, the effect of date pit flour (DPF) as a fat replacer in biscuits at different concentrations (10, 20, 30, and 40% wt/wt) was explored. The proximate,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 46 publications
3
11
0
Order By: Relevance
“…As a result, the enhancement of food products with fiber content is a hot topic in the food industry, and it creates an equal opportunity for food reformulation [ 34 ]. A similar observation of an increase in protein and fiber contents was reported by Saeed et al [ 32 ] when different ratios of DPF were incorporated in wheat flour. Lipid content is another essential factor in the proximate analysis.…”
Section: Resultssupporting
confidence: 87%
See 1 more Smart Citation
“…As a result, the enhancement of food products with fiber content is a hot topic in the food industry, and it creates an equal opportunity for food reformulation [ 34 ]. A similar observation of an increase in protein and fiber contents was reported by Saeed et al [ 32 ] when different ratios of DPF were incorporated in wheat flour. Lipid content is another essential factor in the proximate analysis.…”
Section: Resultssupporting
confidence: 87%
“…These observations were confirmed further by the findings of Hussain et al [ 10 ], which reported that the high concentration of amylose content in Cordia myxa promotes increased water absorption. One of the main advantages of the addition of DPF in the flour blends was the high content of proteins and fibers [ 32 ], which are well-known sources used to enhance the nutritional profile of food products. The highest increase in protein content was observed in T3, which was followed by T2 and T1.…”
Section: Resultsmentioning
confidence: 99%
“…This phenomenon is applicable to the observations in our study. Moreover, several studies on bakery items, such as bread and biscuits, demonstrated that hardness is mainly due to the interactions between gluten and fibre, where dietary fibre leads to higher water absorption and interferes with gluten development time [41,42]. Bouaziz et al [34] tried incorporating the extracted dietary fibre from date seeds, which resulted in a decrease in bread hardness.…”
Section: Colour Analysismentioning
confidence: 99%
“…This lack of interest conflicts with the high content of valuable compounds in date seeds, which include fiber, unsaturated fatty acids, proteins, phenolic compounds, phytosterols, tocopherols, tocotrienols, carotenes, and minerals ( Habib et al, 2013 ; Wahini, 2016 ; Hilary et al, 2020 ; Echegaray et al, 2021 ). Some authors hypothesized that DSF proteins might originate bioactive peptides and associated DSF to antioxidant and ACE inhibitory activities ( Ambigaipalan et al, 2015 ; Saeed et al, 2021 ). Nevertheless, the addition of non-wheat flours in baked good formulas might lead to losses of acceptability, because of the worsening of sensory and rheology attributes.…”
Section: Introductionmentioning
confidence: 99%